Classification of overweight/obesity among Saudi adolescents relative to lifestyle behaviors using the IOTF or WHO reference standards - Al-Hazzaa, Hazzaa M.; Alhakami, Amal; Alotaibi, Ahlam M. (Frontiers in Pediatrics, 2025)
PurposeTo compare two BMI classifications (the IOTF and WHO references) in assessing overweight/obesity prevalence among Saudi adolescents and to evaluate the ability of the two standards to detect risks of unhealthy lifestyle behaviors.MethodsHealthy Saudi adolescents (15–19 years) were drawn from two data sets (n = 2,263) collected previously in 2009 and 2019, using a random multistage stratified cluster sampling technique. Measurements included weight, height, waist circumference (WC), wais to height ratio (WHtR), and selected lifestyle behaviors, including physical activity (PA), screen time, sleep duration, and dietary habits, using the Arab Teen Lifestyle Study (ATLS) questionnaire.ResultsThe proportions (%) of adolescents classified as underweight, normal weight, overweight, and with obesity varied according to the classification used. The IOTF system produces slightly lower overweight/obesity prevalence than the WHO standards (IOTF: 38.8%; WHO: 40.0%), with females exhibited lower overweight/obesity prevalence than males. The Kappa agreement between overweight/obesity in the two references was high (0.973), with high sensitivity (99.8%) and high specificity (98.0%). Kappa values between central obesity and both IOTF (0.691) and WHO (0.687) were moderate with moderate sensitivity and high specificity. In both classification system, intakes >4 days/week of French fries/potato chips, and chocolates/candy showed higher odds of overweight/obesity.ConclusionAlthough overweight/obesity exhibited high Kappa agreement between the two classifications, variations were observed when estimating the prevalence of BMI classification using IOTF or WHO standards. Selected lifestyle behaviors showed significant associations with overweight/obesity in both classification standards.